Faktor yang Mempengaruhi Perkembangan Perumahan Di Pinggiran Kota (Studi Kasus : Kecamatan Boja, Kabupaten Kendal) - Vinda Adeliana; Zukruf Novandaya; Hafzhi Nur Azmi (JAMBURA GEO EDUCATION JOURNAL, 2023)
Population growth and the activities it carries out make the need for land increase, especially in the city center. Land in the city center which is increasingly limited and expensive is no longer able to be accessed by the community to support its activities so that these activities develop into suburban areas. Boja District is one of the suburban areas affected by the development of the City of Semarang, which is indicated by the growth of residential areas since 2010-2020. The purpose of this research is to find out what factors influence the development of suburban housing, Boja District, Kendal Regency. The analysis technique uses quantitative descriptive. Respondents are people who live in housing in the District of Boja. There are 9 variables used for factor analysis and 100 respondents to be surveyed. The research variables consist of livelihood, level of expenditure, length of stay, area of origin, number of family members, house prices, ease of buying a house, installment costs, and credit terms . This research is studied based on the pattern of housing development in suburban areas and the characteristics of housing residents. The results of this study are that there are 3 factors that influence housing development in Boja District, Kendal Regency, namely socio-economic factors consisting of level of expenditure, regional origin, length of stay and house prices, community consumption factors consisting of number of family members, installment costs and livelihoods, as well as risk factors consisting of the installment period and the ease of buying a house.